Modulação da atividade enzimática e estabilidade da tripsina porcina por carboidratos - Couto, Aurelio dos Santos (2024)
Trypsin is a serine protease with catalytic activity sensitive to its environment, which limits its applications in complex biological systems, high temperatures, or extreme pH conditions. Modulating enzyme activity and stability with carbohydrates emerges as a promising strategy to overcome these restrictions. Thus, the modulation of porcine trypsin activity and stability by different carbohydrates (arabinose, L-rhamnose, beta cyclodextrin, maltose, and fructose) at varying concentrations (1:10, 1:30, 1:60, and 1:100 w/w) was investigated. Enzymatic activity was assessed through biochemical assays, while biophysical methods (UV spectroscopy, foldrate calculation, dynamic light scattering (DLS), and zeta potential) were employed to investigate conformational stability and enzyme supramolecular states. Arabinose and L-rhamnose significantly increased trypsin enzymatic activity at certain concentrations between 1:10 and 1:30 (w/w), whereas the other carbohydrates not only failed to increase activity but also decreased enzyme activity. UV spectroscopy did not reveal significant conformational differences in the protein after carbohydrate addition. Foldrate calculation indicated that trypsin samples with 1:10 w/w arabinose and 1:30 w/w L-rhamnose showed significant conformational changes, suggesting greater stability at these tested concentrations. Aggregate profiling showed an increase in particle diameter with 1:30 w/w L-rhamnose, suggesting interaction between the protein and carbohydrate. Regarding protein surface charge (zeta potential), 1:10 w/w arabinose and 1:30 w/w L-rhamnose exhibited higher readings but did not indicate the ability to prevent supramolecular state formation. L-rhamnose at 1:30 w/w is suggested as the optimal condition to optimize porcine trypsin activity without significantly affecting its colloidal stability. These findings may have important implications for trypsin use across various research and industrial applications. Future studies could explore the underlying molecular mechanisms of carbohydrate-induced trypsin modulation, elucidating the basis for developing more efficient enzyme stabilizers